Dietary fiber intake, stool frequency and colonic transit time in chronic functional constipation in children - Guimarães,E.V. (2001)
The objective of the present study was to evaluate associations between fiber intake, colonic transit time and stool frequency. Thirty-eight patients aged 4 to 14 years were submitted to alimentary evaluation and to measurement of colonic transit time. The median fiber intake of the total sample was age + 10.3 g/day. Only 18.4% of the subjects presented a daily dietary fiber intake below the levels recommended by the American Health Foundation. In this group, the median left colonic transit time was shorter than in the group with higher dietary fiber intake (11 vs 17 h, P = 0.067). The correlation between stool frequency and colonic transit time was negative and weak for left colon (r = -0.3, P = 0.04), and negative and moderate for rectosigmoid and total colon (r = -0.5, P<0.001 and r = -0.5, P<0.001, respectively). The stool frequency was lower in the group with slow transit time (0.8 vs 2.3 per week, P = 0.014). In conclusion, most patients with chronic functional constipation had adequate dietary fiber intake. The negative correlation between stool frequency and colonic transit time increased progressively from proximal segments to distal segments of the colon. Patients with normal and prolonged colonic transit time differ in terms of stool frequency.